Spremljanje razvoja likovne apreciacije pri pouku grafičnega oblikovanja - Kač Nemanič, Martina (Revija za elementarno izobraževanje, 2017)
Contemporary education enables the development of creative expression of students, but the role and importance of innovative didactic approaches in the improvement of art appreciation, as an equally important component of artistic activities in graphic design classes in secondary school, have not been researched so far. In this study, we present the results of a research regarding the influence of an innovative didactic approach from the point of view of improvement of art appreciation abilities. The differences were monitored among the students of the 3rd year (aged 17- 18) in Slovenian secondary schools. We found statistically significant differences in the level of art appreciation improvement in favour of the experimental group. The positive effect of the innovative approach to the improvement of art appreciation suggests that even with minor methodical changes the improvement of art appreciation in secondary school students can be significantly increased.
Keywords: grafično oblikovanje; graphic design; secondary school; srednje šole; set of didactic decisions; metodika; učne metode; art appreciation; development; likovna vzgoja